Groundwater–surface water interactions and resilience to hydrological extremes in a data-sparse arid transboundary river basin: Insights from collaborative groundwater modelling - Syed Md Touhidul Mustafa; Jean-Christophe Comte; Fulvio Franchi; Alessia Matano; Anne F. Van Loon; Sithabile Tirivarombo; Luis Artur; Zareen Bharucha; Annatoria Chinyama; Farisse Chirindja; Rosie Day; Joyce Dube; et al. (Hydrogeology Journal, 2026)
Sustainable groundwater management is key to building resilience to hydrological extremes but remains challenging in data-scarce transboundary river basins. In this study, a transboundary, collaborative, physically based groundwater modelling approach has been developed for the Limpopo River Basin (LRB), which is highly vulnerable to floods and droughts. Monitoring data and model results consistently suggest that prolonged wet periods and floods significantly raised groundwater levels, whereas prolonged droughts decreased them, particularly in the upstream and central regions of the basin characterized by low-storage fractured bedrock aquifers. Groundwater–surface water interactions are greater downstream, where water tables are shallower in unconsolidated superficial materials, and intensify during floods, especially in the central region. Modelling results also suggest that baseflow is less responsive to extremes than groundwater recharge across the LRB, highlighting the groundwater system’s attenuation capacity. The model was subsequently used to assess and discuss a series of co-created management scenarios focused specifically on improving groundwater storage during wet periods for use during dry periods. They included: (1) managed aquifer recharge (MAR), using (1a) injection well(s) next to large dams, (1b) rainwater and runoff harvesting (RRH) and infiltration through local wells, (1c) RRH through local ponds and (1d) small reservoirs (e.g. sand dams); (2) deforestation; (3) afforestation; and (4) increased groundwater abstraction. Scenarios suggest that strategy (1b), when widely applied across the basin, may be the most effective to reduce the risk and impact of floods, droughts, and groundwater depletion by supporting the maintenance of groundwater levels and baseflow, while reducing storm runoff.

Land sparing outperforms land sharing across an elevational gradient in tropical cattle-farming landscapes - Giovanny Pérez; Simon C. Mills; Jacob B. Socolar; Jose M. Ochoa Quintero; Torbjørn Haugaasen; Robert P. Freckleton; Jos Barlow; James. J. Gilroy; David P. Edwards (Biological Conservation, 2026)

The Effects of Land‐Use Dynamics on Avian Phylogenetic Diversity Across Island Ecosystems - Halvina G. Saiya; David P. Edwards; Matthew J. Struebig; David J. I. Seaman; Robby Butarbutar; Nurul L. Winarni; Simon L. Mitchell; Jatna Supriatna; Rob W. Martin; Adi Karya; Robert P. Freckleton (Journal of Biogeography, 2026)
Aim To test whether forest extent and recent forest‐cover change are associated with avian phylogenetic diversity and community‐level evolutionary value across islands. Location Seven islands spanning Borneo and Wallacea in the Malay Archipelago. Taxon Terrestrial birds. Methods We sampled 1410 sites (2010–2022). We calculated phylogenetic diversity (PD), mean phylogenetic distance (MPD), mean nearest taxon distance (MNTD) and their standardised effect sizes (SES), as well as community‐level EDGE (Evolutionarily Distinct and Globally Endangered). Responses to (i) average forest proportion (250‐m radius) and (ii) recent forest‐cover change were analysed with spatial linear mixed‐effects. Results Observed PD showed a negative visual trend with increasing forest proportion, whereas SES PD declined. MPD showed only a weak positive visual trend with forest proportion, whereas SES MPD showed no clear response. Although observed MNTD appeared to increase in the binned visual summaries, both observed MNTD and SES MNTD showed significant negative associations with forest cover in the spatial models, indicating stronger nearest‐neighbour phylogenetic clustering in more forested sites. Effects of recent forest loss (2010–2022) on SES metrics were generally weak and inconsistent. Although PD also declined with decreasing rates of forest change, community‐level EDGE was higher where forest cover was greater, indicating higher average evolutionary distinctiveness and extinction risk. Main Conclusions In this archipelagic system, forest amount is a key correlate of phylogenetic structure and the retention of evolutionarily distinctive, high‐risk lineages. By contrast, recent forest‐cover change showed weaker and more context‐dependent associations. Conserving intact forests remains crucial for safeguarding the evolutionary legacy of island bird communities.

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Petrogenesis and Provenance of Unique Amphibole-Bearing Carbonaceous Chondrite Almahata Sitta 202: Further Evidence for a Ceres-Sized, Water-Rich Parent Body - Cyrena A. Goodrich; Victoria E. Hamilton; Michael E. Zolensky; Noriko Kita; Issaku Kohl; Lauren Tafla; Robert J. Macke; Takahiro Hiroi; Yoko Kebukawa; Wayne Buckley; Jacob B. Setera; Justin I. Simon; et al. (Geochimica et Cosmochimica Acta, 2026)

Timing and amplitude of hydroclimate changes during the last glacial cycle in southwestern North America - Simon D. Steidle; Yuri Dublyansky; Marco Roman; Gina E. Moseley; Kathleen A. Wendt; R. Lawrence Edwards; Christoph Spötl (Quaternary Science Reviews, 2026)

Particulate nitrate over the Northwest Atlantic: Insights gained by comparing airborne AMS and PILS measurements - Soodabeh Namdari; Taiwo Ajayi; Yonghoon Choi; Ewan C. Crosbie; Joshua P. DiGangi; Glenn S. Diskin; Eva-Lou Edwards; Johnathan W. Hair; Christopher A. Hostetler; Simon Kirschler; John B. Nowak; Michael Shook; et al. (Atmospheric Environment, 2026)

Impact of cover cropping on root lesion nematodes (Pratylenchus spp.) and nematode communities in Narcissus fields - Vongai Chekanai; Roy Neilson; David Roberts; Simon G. Edwards; Matthew A. Back (Applied Soil Ecology, 2026)

A Conceptual Framework and Methods for Studying the Connectivity of Fishes - Jordanna N. Bergman; Jessica A. Robichaud; Jasper McCutcheon; Michael T. Booth; Brendan Campbell; Grace A. Casselberry; Cienna R. Cooper; Bronwyn M. Gillanders; Lucas P. Griffin; Edward Hale; Luc LaRochelle; Karen J. Murchie; et al. (Fish and Fisheries, 2026)
Connectivity is a multifaceted concept that has important implications for the management and conservation of marine and freshwater fishes. We developed a conceptual framework that encompasses multiple, interrelated categories of connectedness, including landscape (e.g., structural, functional) connectivity and ecological (e.g., trophic, genetic, demographic) connectivity, that together shape the flow of organisms, energy and information across ecosystems. We also synthesised six key methods that can be used to study connectivity of fishes: (1) telemetry, including satellite, acoustic, radio and passive integrated transponders (PIT), (2) mark‐recapture, (3) environmental tracers, including stable isotopes and otolith‐microchemistry, (4) genetics, (5) community structure analysis and (6) emerging technologies and tools (e.g., remote sensing and artificial intelligence). For each method, we describe the categories of connectivity it can assess and provide real‐world examples where they have been effectively used. We also identify limitations of each method. This article highlights the diverse and evolving toolbox of methods used to assess fish connectivity, underscoring the need for continued collaboration, innovation and integration of new approaches to refine our understanding and address remaining challenges in this critical area of aquatic ecology and fisheries management.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Dispersal of marine plastic litter during tropical cyclones - Edward Roome; Peter Robins; Mark Walton; Evelyn Taboada; Simon Neill (Marine Pollution Bulletin, 2026)

Reconstructing savannah wildfire events using a deep learning framework - Simon Ramsey; Karin Reinke; Andrew Edwards; Simon Jones (Remote Sensing Applications: Society and Environment, 2026)

Subsaturated aerosol hygroscopicity over the northwest Atlantic: Impacts of seasonal factors, offshore location, and clouds - Genevieve Rose Lorenzo; Luke D. Ziemba; Yonghoon Choi; Ewan C. Crosbie; Joshua P. DiGangi; Glenn S. Diskin; Richard A. Ferrare; Simon Kirschler; John B. Nowak; Michael A. Shook; Kenneth L. Thornhill; Christiane Voigt; et al. (Atmospheric Environment, 2026)

Correction to: Granulopoietic Dysregulation in a Patient-Tailored Mouse Model of Barth Syndrome - Elizabeth A. Sierra Potchanant; Maegan L. Capitano; Donna M. Edwards; Baskar Ramdas; Scott Cooper; James Ropa; S. Louise Pay; Aditya Sheth; Paige L. Snider; Hilary J. Vernon; Ngoc-Tung Tran; Reuben Kapur; et al. (Stem Cell Reviews and Reports, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Strong Variation in Land‐Use Change Impacts on Tropical Avian Phylogenetic Diversity Between Ecoregions Highlights the Need to Sample Large Spatial Scales - Giovanny Pérez; Simon C. Mills; Jacob B. Socolar; Jose M. Ochoa Quintero; Robert P. Freckleton; Torbjørn Haugaasen; James J. Gilroy; David P. Edwards (Global Change Biology, 2026)
Forest conversion for agriculture is a major cause of tropical biodiversity loss, but its impacts vary with spatial scale. Higher species turnover in forests than in farmland means that land‐use change causes greater biodiversity loss at broader than at local scales, yet broad‐scale assessments are scarce. Phylogenetic diversity is increasingly prioritised in conservation to protect evolutionary history under global change, yet how deforestation‐driven changes in phylogenetic diversity scale spatially and accumulate in regions of high species turnover remains unclear. We compiled a large field database from across 13 biogeographically diverse regions affected by deforestation for cattle farming, covering most of Colombia, a megadiverse tropical country. Using occupancy models, we estimated bird communities for 1547 (936 observed plus 611 never‐observed) species across ecoregions and nationally in both forest and pasture habitats to quantify changes in phylogenetic diversity metrics and determine whether these impacts are dependent on spatial scale. We found an average loss of 2300 Myr of phylogenetic diversity at the country scale, with most species negatively affected across the phylogeny. Although single regional‐scale relative loss was on average comparable to broader scales, there was high variability between regional units. The latter was especially critical when evaluating metrics of evolutionary distinctiveness, which are key indicators for biodiversity conservation planning. Such underestimation of national‐scale impacts highlights the importance of sampling across multiple regions. Immediate conservation action is needed to safeguard evolutionarily unique species and prevent phylogenetic homogenisation driven by agricultural expansion across spatial scales—a threat often underestimated due to assessments limited to single biogeographic regions.

17Oexcess in Devils Hole calcite: an indicator of equilibrium fractionation and paleo moisture sources - Hagit P. Affek; Eugeni Barkan; Yael Tal; Simon D. Steidle; Kathleen A. Wendt; Christoph Spötl; R. Lawrence Edwards; Ekaterina Fishman; Yuri Dublyansky (Earth and Planetary Science Letters, 2025)

Granulopoietic Dysregulation in a Patient-Tailored Mouse Model of Barth Syndrome - Elizabeth A. Sierra Potchanant; Maegan L. Capitano; Donna M. Edwards; Baskar Ramdas; Scott Cooper; James Ropa; S. Louise Pay; Aditya Sheth; Paige L. Snider; Hilary J. Vernon; Ngoc-Tung Tran; Reuben Kapur; et al. (Stem Cell Reviews and Reports, 2025)
Barth syndrome (BTHS) is an X-linked recessive disorder characterized by cardiomyopathy, skeletal muscle myopathy and fatigue, growth restriction, and neutropenia. Neutropenia increases the risk of life-threatening bacterial infections, a major cause of death in individuals with BTHS. Currently, there is no curative treatment for BTHS or associated neutropenia. The development of therapeutic strategies to correct BTHS-associated neutropenia has been hindered by a limited understanding of the underlying molecular mechanisms involved. BTHS is caused by a mutation in the Tafazzin gene encoding a transacylase required for the maturation of cardiolipin, an inner mitochondrial membrane phospholipid crucial for mitochondrial structure and function. We introduced a BTHS patient’s point mutation ( TAZ D75H ) into the mouse Tafazzin enzyme’s critical acyltransferase site using CRISPR/Cas9 -mediated genome editing, resulting in a patient-tailored point mutant knock-in BTHS model ( Taz D75H ) that expresses a stable mutant Taz D75H protein lacking transacylase activity. Taz D75H mice were then used to investigate how loss of Tafazzin enzymatic activity impacts hematopoiesis. Male Taz D75H mice exhibited impaired granulopoiesis and neutropenia secondary to impaired function of hematopoietic progenitors. Furthermore, they demonstrated age-dependent neutrophil maturation impairment reflecting the variable neutropenia observed in BTHS patients. Additionally, male Taz D75H mice exhibit chronic lymphopenia that persists post Taz D75H bone marrow transplantation. Mechanistically, the TAZ D75H point mutation caused hematopoietic cell mitochondrial dysfunction in patient-derived immortalized TAZ D75H lymphoblasts, increasing reactive oxygen species production and mitochondrial membrane depolarization. Likewise, Cyclosporine A treatment rescued these mitochondrial phenotypes in vitro, confirming TAZ D75H mitochondrial dysfunction. Overall, our findings demonstrate that mitochondrial dysfunction secondary to TAFAZZIN loss of enzymatic function underlies BTHS-associated neutropenia and lymphopenia.

Attenuated but not virulent pseudorabies virus activates porcine bone marrow-derived dendritic cells - Emily C. Ashley; Walter Fuchs; Barbara G. Klupp; Dirk Werling; Simon P. Graham; Jane C. Edwards (Veterinary Immunology and Immunopathology, 2025)

Mitochondria-derived peptide MOTS-c and its role in OSA pathogenesis: a potential therapeutic target? - Bradley A. Edwards; Simon A. Joosten; Shane A. Landry (Sleep and Biological Rhythms, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Tropical Land‐Use Change Disrupts Zeta‐Diversity Across Taxa - Edicson Parra‐Sanchez; Guillaume Latombe; Simon C. Mills; Jacob B. Socolar; Felicity A. Edwards; Diego Martinez‐Revelo; Oscar A. Perez‐Escobar; Robert W. Davies; Christopher G. Bousfield; Gianluca R. Cerullo; Jose Manuel Ochoa‐Quintero; Torbjørn Haugaasen; et al. (Global Change Biology, 2025)
Land‐use change causes community turnover via local extinction and colonisation of species, driving biotic homogenization or heterogenization at larger spatial scales. Quantification of these processes has focused on beta‐diversity metrics, which upweight rarity and overlook the role of widespread species. A key knowledge gap is understanding the impact of land‐use change on both rare and widespread species—zeta‐diversity—allowing the detection of statistical patterns and drivers based on community turnover across space. We sampled bird, dung beetle, and orchid communities in 341 plots across natural (Andean forests and paramo) and transformed habitats (pasturelands) spanning ~270 km north‐to‐south in the Colombian Andes. We detected major losses in species richness following land‐use conversion, which disrupts zeta‐diversity across elevation in two ways. First, biodiversity patterns are rewired such that bird and dung beetle communities become structured by dispersal ability, overriding the effects of natural biogeographical drivers (i.e., elevation) and landscape conditions (i.e., canopy cover). Second, land‐use change causes biotic homogenization across bird communities, with pasture retaining twice as many widespread species than natural habitats, and a four‐fold reduction in widespread dung beetle species pointing to subtractive heterogenization. Orchid communities show high community turnover in both natural and transformed habitat. Our results show that the effect of local deforestation has a doubly devastating impact simplifying communities and reducing widespread species. Transforming natural habitats into anthropogenic landscapes may substantially raise extinction risk for communities composed of both widespread and rare species, especially in orchids as the most sensitive taxon.

Ultraviolet radiation vs air filtration to mitigate virus laden aerosol in an occupied clinical room - Shane A. Landry; Milan Jamriska; Vinay J. Menon; Leo Yi Yang Lee; Isabelle Magnin-Bougma; Dinesh Subedi; Jeremy J. Barr; Jason Monty; Kevin Kevin; Ajith Gunatilaka; Michelle Delaire; Guy B. Marks; et al. (Journal of Hazardous Materials, 2025)

Non-serous ovarian cancer in PTEN Hamartoma Tumor Syndrome: additional evidence for increased risk - Ane J. Schei-Andersen; Vera M. Witjes; Janet R. Vos; Arjen R. Mensenkamp; Anne van Altena; Jolanda Schieving; Michiel Simons; Janneke H. M. Schuurs-Hoeijmakers; Muriel A. Adank; Liselotte P. van Hest; Yvette van Ierland; Mirjam de Jong; et al. (Familial Cancer, 2025)
Increased hereditary cancer risk is one of the hallmarks of PTEN Hamartoma Tumor Syndrome (PHTS) which is caused by a pathogenic germline variant in PTEN . Case reports and some cohort studies have described ovarian cancer (OC) in PHTS patients. Previously, we observed an enrichment of non-serous OC in PHTS compared to sporadic cases (3% vs 1%). However, ovarian cancer is currently not considered a PHTS-related cancer. The aim of this study was to describe five PHTS patients with a pathogenic germline variant in PTEN with non-serous OC. Three of the non-serous OCs were mucinous carcinomas (49, 51 and 52 years) and two were malignant germ cell tumors (8 and 15 years) and all were diagnosed before genetic testing and PHTS diagnosis. In addition to OC, the described patients developed other PHTS-related benign and malignant lesions. We provide further evidence that non-serous ovarian cancer, especially mucinous, endometrioid and malignant germ cell tumors should be further investigated as potential PHTS-related cancers.

Quantifying impacts of seabird bycatch using genetic assignment: A case study of black-footed albatross in U.S. fisheries - Jessie N. Beck; Diana S. Baetscher; Claire Tobin; Scott V. Edwards; Simon Yung Wa Sin; Shannon Fitzgerald; Vanessa J. Tuttle; John Peschon; Wesley A. Larson (Biological Conservation, 2025)

Comparative Transcriptomics Reveals the Molecular Mechanisms of Maize in Response to Downy Mildew Disease Caused by Peronosclerospora philippinensis (Weston) Shaw - Edward Cedrick J. Fernandez; Eliza Vie M. Simon-Ada; Jay-Vee S. Mendoza; Anand Noel C. Manohar; Roanne R. Gardoce; Tonette P. Laude; Fe M. Dela Cueva; Darlon V. Lantican (Plant Molecular Biology Reporter, 2025)

Magma storage and transport beneath the near-rift Fjallgarðar Volcanic Ridge, Northeast Iceland - Noëmi Löw; Sæmundur A. Halldórsson; Christoph Beier; Enikő Bali; Simon Matthews; Guðmundur H. Guðfinnsson; Edward W. Marshall; Jóhann Helgason; Eemu Ranta; Adam Abersteiner; Jaime D. Barnes; Alberto Caracciolo (Contributions to Mineralogy and Petrology, 2025)

Proteomic Analysis of Chronic Binge Alcohol-Induced Hippocampal and Anterior Cingulate Cortex Neuroadaptations in Simian Immunodeficiency Virus (SIV)-Infected Female Rhesus Macaques - Taylor Fitzpatrick-Schmidt; Amirsalar Mansouri; Jiri Adamec; Jennifer Klein; Larry Coleman; Kimberly N. Edwards; Liz Simon; Patricia E. Molina; Michael C. Salling; Scott Edwards (Journal of Neuroimmune Pharmacology, 2025)

Machine learning on national shopping data reliably estimates childhood obesity prevalence and socio-economic deprivation - Gavin Long; Georgiana Nica-Avram; John Harvey; Evgeniya Lukinova; Roberto Mansilla; Simon Welham; Gregor Engelmann; Elizabeth Dolan; Kuzivakwashe Makokoro; Michelle Thomas; Edward Powell; James Goulding (Food Policy, 2025)

Multiscale modelling and infection probability of SARS-CoV-2 transmission in a typical lecture theatre - Mei Yan Chong; Hui An; Peng Cheng Wang; Chew Beng Soh; Szu-Cheng Chien; Edward Reuben Roch; Jun Jie Koh; Simon Ching Man Yu (Building and Environment, 2025)

Evaluating SWOT's interferometric capabilities for mapping intertidal topography - Edward Salameh; Damien Desroches; Julien Deloffre; Roger Fjørtoft; Ernesto Tonatiuh Mendoza; Imen Turki; Laurent Froideval; Romain Levaillant; Simon Déchamps; Nicolas Picot; Benoit Laignel; Frédéric Frappart (Remote Sensing of Environment, 2024)

A comprehensive analysis of new particle formation across the northwest Atlantic: Analysis of ACTIVATE airborne data - Soodabeh Namdari; Taiwo Ajayi; Yonghoon Choi; Ewan C. Crosbie; Joshua P. DiGangi; Glenn S. Diskin; Simon Kirschler; Hongyu Liu; John B. Nowak; Michael A. Shook; Cassidy Soloff; Kenneth L. Thornhill; et al. (Atmospheric Environment, 2024)

A sustainable blue economy may not be possible in Tanzania without cutting emissions - Ana M. Queirós; Elizabeth Talbot; Flower E. Msuya; Baraka Kuguru; Narriman Jiddawi; Shigalla Mahongo; Yohana Shaghude; Christopher Muhando; Elias Chundu; Zoe Jacobs; Sevrine Sailley; Elina A. Virtanen; et al. (Science of The Total Environment, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

In-situ observations of resident space objects with the CHEOPS space telescope - Nicolas Billot; Stephan Hellmich; Willy Benz; Andrea Fortier; David Ehrenreich; Christopher Broeg; Alexis Heitzmann; Anja Bekkelien; Alexis Brandeker; Yann Alibert; Roi Alonso; Tamas Bárczy; et al. (Journal of Space Safety Engineering, 2024)

Long-term mercury accumulation and climate reconstruction of an Australian alpine lake during the late Quaternary - Margot Aurel Schneider; Larissa Schneider; Haidee Cadd; Zoë A. Thomas; Antonio Martinez-Cortizas; Simon Edward Connor; Georgia L. Stannard; Simon Graeme Haberle (Global and Planetary Change, 2024)

Resistance response of yellow maize inbreds and F1 crosses against Philippine downy mildew [Peronosclerospora philippinensis (Weston) C.G. Shaw] - Eliza Vie M. Simon-Ada; Jay-Vee S. Mendoza; Edward Cedrick J. Fernandez; John Paolo P. Nuñez; Fe M. Dela Cueva; Anand Noel C. Manohar; Roanne R. Gardoce; Tonette P. Laude; Darlon V. Lantican (Crop Protection, 2024)

Experimental and theoretical constraints on lithium isotope fractionation during brine evaporation and halite precipitation - Yongjie Lin; Marcello Merli; Paolo Censi; Simon A.T. Redfern; Yue Zhao; Qing-Zhu Yin; Mianping Zheng; Xudong Yu; Yongsheng Zhang; William J. Knapp; Edward T. Tipper (Geochimica et Cosmochimica Acta, 2024)

Biosecurity Within Poultry Farms in the Ashanti Region of Ghana - Kwaku Adomako; Bertha Yayra Ahiabli; Jacob Alhassan Hamidu; Oscar Simon Olympio; Edward Yeboah (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2024)

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

Well-to-wheels scenarios for 2050 carbon-neutral road transport in the EU - Jette Krause; Marta Yugo; Zissis Samaras; Simon Edwards; Georgios Fontaras; Roland Dauphin; Peter Prenninger; Stephan Neugebauer (Journal of Cleaner Production, 2024)

Global responses to the COVID-19 pandemic by recreational anglers: considerations for developing more resilient and sustainable fisheries - J. Robert Britton; Adrian C. Pinder; Josep Alós; Robert Arlinghaus; Andy J. Danylchuk; Wendy Edwards; Kátia M. F. Freire; Casper Gundelund; Kieran Hyder; Ivan Jarić; Robert Lennox; Wolf-Christian Lewin; et al. (Reviews in Fish Biology and Fisheries, 2023)
The global COVID-19 pandemic resulted in many jurisdictions implementing orders restricting the movements of people to inhibit virus transmission, with recreational angling often either not permitted or access to fisheries and/or related infrastructure being prevented. Following the lifting of restrictions, initial angler surveys and licence sales suggested increased participation and effort, and altered angler demographics, but with evidence remaining limited. Here, we overcome this evidence gap by identifying temporal changes in angling interest, licence sales, and angling effort in world regions by comparing data in the ‘pre-pandemic’ (up to and including 2019); ‘acute pandemic’ (2020) and ‘COVID-acclimated’ (2021) periods. We then identified how changes can inform the development of more resilient and sustainable recreational fisheries. Interest in angling (measured here as angling-related internet search term volumes) increased substantially in all regions during 2020. Patterns in licence sales revealed marked increases in some countries during 2020 but not in others. Where licence sales increased, this was rarely sustained in 2021; where there were declines, these related to fewer tourist anglers due to movement restrictions. Data from most countries indicated a younger demographic of people who participated in angling in 2020, including in urban areas, but this was not sustained in 2021. These short-lived changes in recreational angling indicate efforts to retain younger anglers could increase overall participation levels, where efforts can target education in appropriate angling practices and create more urban angling opportunities. These efforts would then provide recreational fisheries with greater resilience to cope with future global crises, including facilitating the ability of people to access angling opportunities during periods of high societal stress.

Modeling microclimatic effects of trees and green roofs/façades in ENVI-met: Sensitivity tests and proposed model library - Zhixin Liu; Ka Yuen Cheng; Tim Sinsel; Helge Simon; C.Y. Jim; Tobi Eniolu Morakinyo; Yueyang He; Shi Yin; Wanlu Ouyang; Yuan Shi; Edward Ng (Building and Environment, 2023)

Avian biodiversity losses from grazing of high Andean páramo - Simon C. Mills; Edicson Parra Sanchez; Jacob B. Socolar; Chris Bousfield; Bryn Coffey; Jos Barlow; Jose Manuel Ochoa Quintero; Torbjørn Haugaasen; David P. Edwards (Biological Conservation, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Challenges in cybersecurity: Lessons from biological defense systems - Edward Schrom; Ann Kinzig; Stephanie Forrest; Andrea L. Graham; Simon A. Levin; Carl T. Bergstrom; Carlos Castillo-Chavez; James P. Collins; Rob J. de Boer; Adam Doupé; Roya Ensafi; Stuart Feldman; et al. (Mathematical Biosciences, 2023)

Coral adaptive capacity insufficient to halt global transition of coral reefs into net erosion under climate change - Christopher Edward Cornwall; Steeve Comeau; Simon D. Donner; Chris Perry; John Dunne; Ruben van Hooidonk; James S. Ryan; Cheryl A. Logan (Global Change Biology, 2023)
Projecting the effects of climate change on net reef calcium carbonate production is critical to understanding the future impacts on ecosystem function, but prior estimates have not included corals' natural adaptive capacity to such change. Here we estimate how the ability of symbionts to evolve tolerance to heat stress, or for coral hosts to shuffle to favourable symbionts, and their combination, may influence responses to the combined impacts of ocean warming and acidification under three representative concentration pathway (RCP) emissions scenarios (RCP2.6, RCP4.5 and RCP8.5). We show that symbiont evolution and shuffling, both individually and when combined, favours persistent positive net reef calcium carbonate production. However, our projections of future net calcium carbonate production (NCCP) under climate change vary both spatially and by RCP. For example, 19%–35% of modelled coral reefs are still projected to have net positive NCCP by 2050 if symbionts can evolve increased thermal tolerance, depending on the RCP. Without symbiont adaptive capacity, the number of coral reefs with positive NCCP drops to 9%–13% by 2050. Accounting for both symbiont evolution and shuffling, we project median positive NCPP of coral reefs will still occur under low greenhouse emissions (RCP2.6) in the Indian Ocean, and even under moderate emissions (RCP4.5) in the Pacific Ocean. However, adaptive capacity will be insufficient to halt the transition of coral reefs globally into erosion by 2050 under severe emissions scenarios (RCP8.5).

Retaining natural vegetation to safeguard biodiversity and humanity - Jeremy S. Simmonds; Andres Felipe Suarez‐Castro; April E. Reside; James E. M. Watson; James R. Allan; Scott C. Atkinson; Pasquale Borrelli; Nigel Dudley; Stephen Edwards; Richard A. Fuller; Edward T. Game; Simon Linke; et al. (Conservation Biology, 2023)
Global efforts to deliver internationally agreed goals to reduce carbon emissions, halt biodiversity loss, and retain essential ecosystem services have been poorly integrated. These goals rely in part on preserving natural (e.g., native, largely unmodified) and seminatural (e.g., low intensity or sustainable human use) forests, woodlands, and grasslands. To show how to unify these goals, we empirically derived spatially explicit, quantitative, area‐based targets for the retention of natural and seminatural (e.g., native) terrestrial vegetation worldwide. We used a 250‐m‐resolution map of natural and seminatural vegetation cover and, from this, selected areas identified under different international agreements as being important for achieving global biodiversity, carbon, soil, and water targets. At least 67 million km 2 of Earth's terrestrial vegetation (∼79% of the area of vegetation remaining) required retention to contribute to biodiversity, climate, soil, and freshwater conservation objectives under 4 United Nations’ resolutions. This equates to retaining natural and seminatural vegetation across at least 50% of the total terrestrial (excluding Antarctica) surface of Earth. Retention efforts could contribute to multiple goals simultaneously, especially where natural and seminatural vegetation can be managed to achieve cobenefits for biodiversity, carbon storage, and ecosystem service provision. Such management can and should co‐occur and be driven by people who live in and rely on places where natural and sustainably managed vegetation remains in situ and must be complemented by restoration and appropriate management of more human‐modified environments if global goals are to be realized.

Long‐term trajectories of non‐native vegetation on islands globally - Anna Walentowitz; Bernd Lenzner; Franz Essl; Nichola Strandberg; Alvaro Castilla‐Beltrán; José María Fernández‐Palacios; Svante Björck; Simon Connor; Simon G. Haberle; Karl Ljung; Matiu Prebble; Janet M. Wilmshurst; et al. (Ecology Letters, 2023)
Human‐mediated changes in island vegetation are, among others, largely caused by the introduction and establishment of non‐native species. However, data on past changes in non‐native plant species abundance that predate historical documentation and censuses are scarce. Islands are among the few places where we can track human arrival in natural systems allowing us to reveal changes in vegetation dynamics with the arrival of non‐native species. We matched fossil pollen data with botanical status information (native, non‐native), and quantified the timing, trajectories and magnitude of non‐native plant vegetational change on 29 islands over the past 5000 years. We recorded a proportional increase in pollen of non‐native plant taxa within the last 1000 years. Individual island trajectories are context‐dependent and linked to island settlement histories. Our data show that non‐native plant introductions have a longer and more dynamic history than is generally recognized, with critical implications for biodiversity baselines and invasion biology.

Species-level dataset is required for setting biodiversity conservation priorities for freshwater macroinvertebrates in Melbourne streams - Edward Tsyrlin; Melissa Carew; Ary A. Hoffmann; Simon Linke; Rhys A. Coleman (Journal of Environmental Management, 2023)

Whole‐genome phylogeography of the blue‐faced honeyeater ( Entomyzon cyanotis ) and discovery and characterization of a neo‐Z chromosome - John T. Burley; Sophia C. M. Orzechowski; Simon Yung Wa Sin; Scott V. Edwards (Molecular Ecology, 2023)
Whole‐genome surveys of genetic diversity and geographic variation often yield unexpected discoveries of novel structural variation, which long‐read DNA sequencing can help clarify. Here, we report on whole‐genome phylogeography of a bird exhibiting classic vicariant geographies across Australia and New Guinea, the blue‐faced honeyeater ( Entomyzon cyanotis ), and the discovery and characterization of a novel neo‐Z chromosome by long‐read sequencing. Using short‐read genome‐wide SNPs, we inferred population divergence events within E. cyanotis across the Carpentarian and other biogeographic barriers during the Pleistocene (~0.3–1.7 Ma). Evidence for introgression between nonsister populations supports a hypothesis of reticulate evolution around a triad of dynamic barriers around Pleistocene Lake Carpentaria between Australia and New Guinea. During this phylogeographic survey, we discovered a large (134 Mbp) neo‐Z chromosome and we explored its diversity, divergence and introgression landscape. We show that, as in some sylvioid passerine birds, a fusion occurred between chromosome 5 and the Z chromosome to form a neo‐Z chromosome; and in E. cyanotis , the ancestral pseudoautosomal region (PAR) appears nonrecombinant between Z and W, along with most of the fused chromosome 5. The added recombination‐suppressed portion of the neo‐Z (~37.2 Mbp) displays reduced diversity and faster population genetic differentiation compared with the ancestral‐Z. Yet, the new PAR (~17.4 Mbp) shows elevated diversity and reduced differentiation compared to autosomes, potentially resulting from introgression. In our case, long‐read sequencing helped clarify the genomic landscape of population divergence on autosomes and sex chromosomes in a species where prior knowledge of genome structure was still incomplete.

Climate driven shifts in the synchrony of apple (Malus x domestica Borkh.) flowering and pollinating bee flight phenology - Chris Wyver; Simon G. Potts; Rowan Edwards; Mike Edwards; Deepa Senapathi (Agricultural and Forest Meteorology, 2023)

Understanding the links between snoring, OSA and aortic root pathologies in Marfan syndrome - Bradley A. Edwards; Simon A. Joosten (Sleep and Biological Rhythms, 2023)

High sensitivity of tropical forest birds to deforestation at lower altitudes - Simon C. Mills; Jacob B. Socolar; Felicity A. Edwards; Edicson Parra; Diego E. Martínez‐Revelo; Jose Manuel Ochoa Quintero; Torbjørn Haugaasen; Robert P. Freckleton; Jos Barlow; David P. Edwards (Ecology, 2023)
Habitat conversion is a major driver of tropical biodiversity loss, but its effects are poorly understood in montane environments. While community‐level responses to habitat loss display strong elevational dependencies, it is unclear whether these arise via elevational turnover in community composition and interspecific differences in sensitivity or elevational variation in environmental conditions and proximity to thermal thresholds. Here we assess the relative importance of inter‐ and intraspecific variation across the elevational gradient by quantifying how 243 forest‐dependent bird species vary in sensitivity to landscape‐scale forest loss across a 3000‐m elevational gradient in the Colombian Andes. We find that species that live at lower elevations are strongly affected by loss of forest in the nearby landscape, while those at higher elevations appear relatively unperturbed, an effect that is independent of phylogeny. Conversely, we find limited evidence of intraspecific elevational gradients in sensitivity, with populations displaying similar sensitivities to forest loss, regardless of where they exist in a species' elevational range. Gradients in biodiversity response to habitat loss thus appear to arise via interspecific gradients in sensitivity rather than proximity to climatically limiting conditions.

Fusarium langsethiae and mycotoxin contamination in oat grain differed with growth stage at inoculation - Heidi Udnes Aamot; Hesam Mousavi; Jafar Razzaghian; Guro Brodal; Michael Sulyok; Rudolf Krska; Simon G. Edwards; Ingerd S. Hofgaard (European Journal of Plant Pathology, 2022)
High levels of mycotoxins are occasionally observed in Norwegian oat grain lots. Mycotoxins of primary concern in Norwegian oats are deoxynivalenol (DON) produced by Fusarium graminearum and HT2- and T2-toxins (HT2 + T2) produced by Fusarium langsethiae . Improved understanding of the epidemiology of Fusarium spp. is important for the development of measures to control mycotoxins. We studied the susceptibility to F. langsethiae after inoculation at early (booting, heading, flowering) or late (flowering, milk, dough) growth stages in three oat varieties in greenhouse experiments. The varieties had previously shown different levels of resistance to F. graminearum : Odal, Vinger (both moderately resistant), and Belinda (susceptible). The level of F. langsethiae DNA and HT2 + T2 were measured in harvested grain. In addition, we observed differences in aggressiveness (measured as the level of F. langsethiae DNA in grain) between F. langsethiae isolates after inoculation of oats at flowering. Substantial levels of F. langsethiae DNA (mean ≥ 138 pg per μg plant DNA) and HT2 + T2 (≥348 μg/kg) were detected in grain harvested from oats that were spray-inoculated at heading or later stages, but not at booting (mean ≤ 10 pg/μg and ≤ 25 μg/kg, respectively), suggesting that oats are susceptible to F. langsethiae from heading and onwards. Vinger was the most resistant variety to F. langsethiae /HT2 + T2, whereas Odal and Belinda were relatively susceptible. We observed that late inoculations yielded high levels of other trichothecene A metabolites (mean sum of metabolites of 35–1048 μg/kg) in addition to HT2 + T2, in harvested grain, an indication that infections close to harvest may pose a further risk to food and feed safety.

Krill biomass estimation: Sampling and measurement variability - Fiona Bairstow; Sven Gastauer; Simon Wotherspoon; C. Tom A. Brown; So Kawaguchi; Tom Edwards; Martin J. Cox (Frontiers in Marine Science, 2022)
Krill are the subject of growing commercial fisheries and therefore fisheries management is necessary to ensure long-term sustainability. Krill catch limits, set by Commission for the Conservation of Antarctic Marine Living Resources, are based on absolute krill biomass, estimated from acoustic-trawl surveys. In this work, we develop a method for determining an error budget for acoustic-trawl surveys of krill which includes sampling and measurement variability. We use our error budget method to examine the sensitivity of biomass estimates to parameters in acoustic target strength (TS) models, length frequency distribution and length to wetmass relationships derived from net data. We determined that the average coefficient of variation ( CV ) of estimated biomass was 17.7% and the average CV due from scaling acoustic observations to biomass density was 5.3%. We found that a large proportion of the variability of biomass estimates is due to the krill orientation distribution, a parameter in the TS model. Orientation distributions with narrow standard deviations were found to emphasise the results of nulls in the TS to length relationship, which has to potential to lead to biologically implausible results.

Long‐term drivers and timing of accelerated vegetation changes in African biomes and their management implications - Matthew Adesanya Adeleye; Simon Edward Connor; Simon Graeme Haberle; Sarah Ivory; Peter Adegbenga Adeonipekun (Global Ecology and Biogeography, 2022)
Aim Owing to its diverse bioclimatic zones, long human history and intense anthropogenic impacts, Africa provides a model system for studying how global terrestrial ecosystems might respond to accelerated socio‐environmental stress. Africa is particularly vulnerable to climate change and human impact, and insufficient baseline data hamper current environmental management efforts. Using palaeoecological data, we seek to identify the timing, pace and drivers of change in African biomes on a long‐term scale to inform current ecosystem management frameworks on the continent. Location Africa. Time period 0–12 ka. Major taxa studied African biomes. Methods Sixty‐four pollen records across Africa and nearby sites were retrieved from multiple databases/sources and grouped into biomes. Turnover (quantified using the squared chord distance dissimilarity metric) and rarefaction analyses were conducted on pollen records in each biome group to reconstruct regional temporal vegetation turnover and richness. Reconstructed vegetation turnover and richness were compared with independent records of climate, fire and human activity to identify possible drivers of change. Results We found that the most stable biomes were those with the greatest floristic richness. Southern Africa's mediterranean‐type (SAM) ecosystems were the most stable and northern Africa's mediterranean‐type (NAM) ecosystems were the most unstable (mainly owing to fire). Tropical savannas (TS) and SAM ecosystems expressed the most sensitivity to climatic shifts from ≥6 ka, whereas tropical forests (TF) were relatively stable before human activities intensified from c . 2 ka. Floristic richness also declined across the tropics from c . 2 ka. Main conclusions Our analysis pinpoints NAM ecosystems as undergoing the fastest acceleration in turnover on the continent in response to fire, whereas TF and TS have been undergoing unprecedented changes in biodiversity in the last 2,000 years. We expect further changes in biodiversity where climate becomes warmer and drier and where human impacts are novel and rapid in comparison to long‐term baselines.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Environmental change during the last glacial on an ancient land bridge of southeast Australia - Matthew Adesanya Adeleye; Simon Graeme Haberle; David McWethy; Simon Edward Connor; Janelle Stevenson (Journal of Biogeography, 2021)
Aim The Last Glacial Maximum (LGM) remains an enigmatic period in southeast Australia due to the limited spatial and temporal resolution of its palaeoclimatic records. A major feature of the LGM landscape was the existence of the Bassian Land Bridge, joining Tasmania with the mainland of Australia during periods of low sea level, and potentially facilitating increased biotic movement between these regions. To better understand biogeographical changes on the land bridge and in southeast Australia generally during the LGM, we present a 35 ka‐year palaeoecological record from one of the larger islands of Bass Strait. Location Bass Strait, southeast Australia. Taxon Eucalyptus , Poaceae, Monotoca , Myriophyllum , Zygnemataceae, Botryococcus , Pediastrum . Methods Pollen, charcoal, and non‐pollen palynomorphs were analysed in a 1.75‐m sediment core from truwana/Cape Barren Island, Bass Strait, to reconstruct changes in vegetation, fire regimes and lake levels on the Bassian Land Bridge. Results were then compared to existing palaeoenvironmental studies in the region to develop a broader context of the prevailing land bridge environment and the potential influence on biotic dispersals in Australia during the last glacial period. Results Results suggest a major vegetation shift on the Bassian Land Bridge in response to the establishment of the LGM climate, with grassland expansion at the expense of woodland from ~29–11 ka. Floristic richness, biomass burned and lake levels also markedly decreased through this period, with the driest interval being ~25–18 ka. Dryland herbaceous taxa dispersed between the mainland and Tasmania when the landbridge was fully exposed. Main conclusions In agreement with previous studies, our results show that the dry grassland that dominated southeast Australia (and Southern Hemisphere mid‐latitude areas) during the LGM also extended across the Bassian Land Bridge. The prevailing environment on the land bridge is likely to have exerted a selective influence on biotic dispersals in Australia during glacial periods.

Assessing Long-Term Ecological Changes in Wetlands of the Bass Strait Islands, Southeast Australia: Palaeoecological Insights and Management Implications - Matthew Adesanya Adeleye; Simon Graeme Haberle; Stephen Harris; Simon Edward Connor; Janelle Stevenson (Wetlands, 2021)

Extensive human‐mediated jump dispersal within and across the native and introduced ranges of the invasive termite Reticulitermes flavipes - Pierre‐André Eyer; Alexander J. Blumenfeld; Laura N. L. Johnson; Elfie Perdereau; Phillip Shults; Shichen Wang; Franck Dedeine; Simon Dupont; Anne‐Geneviève Bagnères; Edward L. Vargo (Molecular Ecology, 2021)
As native ranges are often geographically structured, invasive species originating from a single source population only carry a fraction of the genetic diversity present in their native range. The invasion process is thus often associated with a drastic loss of genetic diversity resulting from a founder event. However, the fraction of diversity brought to the invasive range may vary under different invasion histories, increasing with the size of the propagule, the number of reintroduction events, and/or the total genetic diversity represented by the various source populations in a multiple‐introduction scenario. In this study, we generated a SNP data set for the invasive termite Reticulitermes flavipes from 23 native populations in the eastern United States and six introduced populations throughout the world. Using population genetic analyses and approximate Bayesian computation random forest, we investigated its worldwide invasion history. We found a complex invasion pathway with multiple events out of the native range and bridgehead introductions from the introduced population in France. Our data suggest that extensive long‐distance jump dispersal appears common in both the native and introduced ranges of this species, probably through human transportation. Overall, our results show that similar to multiple introduction events into the invasive range, admixture in the native range prior to invasion can potentially favour invasion success by increasing the genetic diversity that is later transferred to the introduced range.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Pantropical variability in tree crown allometry - Grace Jopaul Loubota Panzou; Adeline Fayolle; Tommaso Jucker; Oliver L. Phillips; Stephanie Bohlman; Lindsay F. Banin; Simon L. Lewis; Kofi Affum‐Baffoe; Luciana F. Alves; Cécile Antin; Eric Arets; Luzmila Arroyo; et al. (Global Ecology and Biogeography, 2021)
Aim Tree crowns determine light interception, carbon and water exchange. Thus, understanding the factors causing tree crown allometry to vary at the tree and stand level matters greatly for the development of future vegetation modelling and for the calibration of remote sensing products. Nevertheless, we know little about large‐scale variation and determinants in tropical tree crown allometry. In this study, we explored the continental variation in scaling exponents of site‐specific crown allometry and assessed their relationships with environmental and stand‐level variables in the tropics. Location Global tropics. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 87,737 trees distributed among 245 forest and savanna sites across the tropics, we fitted site‐specific allometric relationships between crown dimensions (crown depth, diameter and volume) and stem diameter using power‐law models. Stand‐level and environmental drivers of crown allometric relationships were assessed at pantropical and continental scales. Results The scaling exponents of allometric relationships between stem diameter and crown dimensions were higher in savannas than in forests. We identified that continental crown models were better than pantropical crown models and that continental differences in crown allometric relationships were driven by both stand‐level (wood density) and environmental (precipitation, cation exchange capacity and soil texture) variables for both tropical biomes. For a given diameter, forest trees from Asia and savanna trees from Australia had smaller crown dimensions than trees in Africa and America, with crown volumes for some Asian forest trees being smaller than those of trees in African forests. Main conclusions Our results provide new insight into geographical variability, with large continental differences in tropical tree crown allometry that were driven by stand‐level and environmental variables. They have implications for the assessment of ecosystem function and for the monitoring of woody biomass by remote sensing techniques in the global tropics.

An agenda for ethics and justice in adaptation to climate change - Morten Fibieger Byskov; Keith Hyams; Poshendra Satyal; Isabelle Anguelovski; Lisa Benjamin; Sophie Blackburn; Maud Borie; Simon Caney; Eric Chu; Gareth Edwards; Kristel Fourie; Arabella Fraser; et al. (Climate and Development, 2021)

Dietary intake, eating behavior and physical activity in individuals with and without obstructive sleep apnea - Caroline J. Beatty; Shane A. Landry; Joy Lee; Simon A. Joosten; Anthony Turton; Denise M. O’Driscoll; Ai-Ming Wong; Luke Thomson; Bradley A. Edwards; Garun S. Hamilton (Sleep and Biological Rhythms, 2021)

Correction to: Transition Periods in the Diurnally-Varying Atmospheric Boundary Layer Over Land - Wayne M. Angevine; John M. Edwards; Marie Lothon; Margaret A. LeMone; Simon R. Osborne (Boundary-Layer Meteorology, 2020)

Transition Periods in the Diurnally-Varying Atmospheric Boundary Layer Over Land - Wayne M. Angevine; John M. Edwards; Marie Lothon; Margaret A. LeMone; Simon R. Osborne (Boundary-Layer Meteorology, 2020)

Public Perceptions of Mangrove Forests Matter for Their Conservation - Farid Dahdouh-Guebas; Gordon N. Ajonina; A. Aldrie Amir; Dominic A. Andradi-Brown; Irfan Aziz; Thorsten Balke; Edward B. Barbier; Stefano Cannicci; Simon M. Cragg; Marília Cunha-Lignon; David J. Curnick; Carlos M. Duarte; et al. (Frontiers in Marine Science, 2020)

Evolution of the African slippery frogs (Anura: Conraua ), including the world’s largest living frog - David C. Blackburn; Stuart V. Nielsen; Michael F. Barej; Joseph Doumbia; Mareike Hirschfeld; N’Goran G. Kouamé; Dwight Lawson; Simon Loader; Caleb Ofori‐Boateng; Edward L. Stanley; Mark‐Oliver Rödel (Zoologica Scripta, 2020)
Although Conraua goliath is well known as the largest living frog species, the diversity and evolution of the genus Conraua across sub‐Saharan Africa remain poorly understood. We present multilocus phylogenetic analyses of the six currently recognized species that provide insights into divergence times, biogeography, body size evolution and undescribed species. An analysis of divergence times demonstrates that crown‐group Conraua arose some time during the latest Oligocene to mid‐Miocene followed by divergence into major lineages in the mid‐Miocene that may reflect the fragmentation of widespread tropical forests in Africa that began at this time. We find three pairs of sister species, C. crassipes + C. beccarii , C. alleni + C. derooi and C. goliath + C. robusta , each of which diverged during the Miocene. These relationships reject phylogenetic hypotheses based solely on biogeography as the geographically peripheral C. beccarii from north‐eastern Africa is nested within western African species and the Central African species do not form a clade. Our species delimitation analyses provide support for undescribed species in C. alleni , C. beccarii and C. derooi , and possibly C. crassipes , suggesting that the current taxonomy substantially underestimates species diversity. There is no clear directional trend of either increasing or decreasing body size in Conraua and the three largest species do not form a clade. With a robust phylogenetic hypothesis in hand, further field‐based studies are needed to understand the evolution of morphology and life history in this charismatic African anuran clade.

Old growth Afrotropical forests critical for maintaining forest carbon - John R. Poulsen; Vincent P. Medjibe; Lee J. T. White; Zewei Miao; Ludovic Banak‐Ngok; Chris Beirne; Connie J. Clark; Aida Cuni‐Sanchez; Mathias Disney; Jean‐Louis Doucet; Michelle E. Lee; Simon L. Lewis; et al. (Global Ecology and Biogeography, 2020)
Aim Large trees [≥ 70 cm diameter at breast height (DBH)] contribute disproportionately to aboveground carbon stock (AGC) across the tropics but may be vulnerable to changing climate and human activities. Here we determine the distribution, drivers and threats to large trees and high carbon forest. Location Central Africa. Time period Current. Major taxa studied Trees. Methods Using Gabon's new National Resource Inventory of 104 field sites, AGC was calculated from 67,466 trees from 578 species and 97 genera. Power and Michaelis–Menten models assessed the contribution of large trees to AGC. Environmental and anthropogenic drivers of AGC, large trees, and stand variables were modelled using Akaike’s information criterion (AIC) weights to calculate average regression coefficients for all p ossible models. Results Mean AGC for trees ≥ 10 cm DBH in Gabonese forestlands was 141.7 Mg C/ha, with averages of 166.6, 171.3 and 96.6 Mg C/ha in old growth, concession and secondary forest. High carbon forests occurred where large trees are most abundant: 31% of AGC was stored in large trees (2.3% of all stems). Human activities largely drove variation in AGC and large trees, but climate and edaphic conditions also determined stand variables (basal area, tree height, wood density, stem density). AGC and large trees increased with distance from human settlements; AGC was 40% lower in secondary than primary and concession forests and 33% higher in protected than non‐managed areas. Main conclusions AGC and large trees were negatively associated with human activities, highlighting the importance of forest management. Redefining large trees as ≥ 50 cm DBH (4.3% more stems) would account for 20% more AGC. This study demonstrates that protecting relatively undisturbed forests can be disproportionately effective in conserving carbon and suggests that including sustainable forestry in programs like reduced emissions for deforestation and forest degradation could maintain carbon dense forests in logging concessions that are a large proportion of remaining Central African forests.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Towards an African Light Source - Simon H. Connell; Sekazi K. Mtingwa; Tabbetha Dobbins; Nkem Khumbah; Brian Masara; Edward P. Mitchell; Lawrence Norris; Prosper Ngabonziza; Tshepo Ntsoane; Herman Winick (Biophysical Reviews, 2019)

Multiscale patterns of rarity in fungi, inferred from fruiting records - Alan C. Gange; Lewis P. Allen; Aline Nussbaumer; Edward G. Gange; Carrie Andrew; Simon Egli; Beatrice Senn‐Irlet; Lynne Boddy (Global Ecology and Biogeography, 2019)
Aim It is unknown whether fungi show similar trends to other organisms in their macroecological patterns of abundance and spatial distribution. Here, we investigated fungal abundance–occupancy relationships to determine whether fungi that are common at a local scale tend to be more widely distributed. Location UK and Switzerland. Time period 1950–2014. Major taxa studied Fungi. Methods We used a local data set of fruiting records of 2,319 species in the UK, accumulated over 65 years, and one from Switzerland of 319 species, spanning 32 years. Using the number of records and occurrence as proxies for abundance, in each case we examined the form of species and rank abundance distributions and compared these with distributions of records in the national databases over the same time. We plotted relationships of the local number of records and regional occupancy and calculated multiscale indices of rarity for all fungal species. Results There was a remarkable congruence in the patterns found in the UK and Switzerland. Regional assemblages are characterized by many rare species, whereas few are common (fitting the lognormal distribution). However, at local scales, distributions best fitted a power law, suggesting that habitat availability or dispersal processes might play important roles. Fungi with a high number of local records are densely distributed nationally, but unlike other organisms, locally rare fungi may also be densely distributed at a wider scale. Main conclusions Fungal fruiting records can be used to infer patterns in fungal distributions. Abundances in local assemblages may be determined by the position of the assemblage in the overall geographical range of each species, dispersal ability and environmental filtering. We advocate the use of multiscale approaches to rarity in future fungal sampling programmes, to provide more reliable information for future conservation policy decisions and fungal biogeography.

Simultaneous‐count models to estimate abundance from counts of unmarked individuals with imperfect detection - Gerard Edward Ryan; Emily Nicholson; Jonathan C. Eames; Thomas N. E. Gray; Robin Loveridge; Simon P. Mahood; Phearun Sum; Michael A. McCarthy (Conservation Biology, 2019)
We developed a method to estimate population abundance from simultaneous counts of unmarked individuals over multiple sites. We considered that at each sampling occasion, individuals in a population could be detected at 1 of the survey sites or remain undetected and used either multinomial or binomial simultaneous‐count models to estimate abundance, the latter being equivalent to an N‐mixture model with one site. We tested model performance with simulations over a range of detection probabilities, population sizes, growth rates, number of years, sampling occasions, and sites. We then applied our method to 3 critically endangered vulture species in Cambodia to demonstrate the real‐world applicability of the model and to provide the first abundance estimates for these species in Cambodia. Our new approach works best when existing methods are expected to perform poorly (i.e., few sites and large variation in abundance among sites) and if individuals may move among sites between sampling occasions. The approach performed better when there were >8 sampling occasions and net probability of detection was high (>0.5). We believe our approach will be useful in particular for simultaneous surveys at aggregation sites, such as roosts. The method complements existing approaches for estimating abundance of unmarked individuals and is the first method designed specifically for simultaneous counts.

Congo Basin peatlands: threats and conservation priorities - Greta C. Dargie; Ian T. Lawson; Tim J. Rayden; Lera Miles; Edward T. A. Mitchard; Susan E. Page; Yannick E. Bocko; Suspense A. Ifo; Simon L. Lewis (Mitigation and Adaptation Strategies for Global Change, 2019)

The effects of training population design on genomic prediction accuracy in wheat - Stefan McKinnon Edwards; Jaap B. Buntjer; Robert Jackson; Alison R. Bentley; Jacob Lage; Ed Byrne; Chris Burt; Peter Jack; Simon Berry; Edward Flatman; Bruno Poupard; Stephen Smith; et al. (Theoretical and Applied Genetics, 2019)

Antibiotic misuse in respiratory tract infections in children and adults—a prospective, multicentre study (TAILORED Treatment) - Chantal B. van Houten; Asi Cohen; Dan Engelhard; John P. Hays; Roger Karlsson; Edward Moore; David Fernández; Racheli Kreisberg; Laurence V. Collins; Wouter de Waal; Karin M. de Winter-de Groot; Tom F. W. Wolfs; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Impact of agronomic factors on fusarium mycotoxins in harvested wheat - Simon G Edwards; Philip Jennings (Food Additives & Contaminants: Part A, 2018)

Modelling glacial lake outburst flood impacts in the Bolivian Andes - Ioannis Kougkoulos; Simon J. Cook; Laura A. Edwards; Leon J. Clarke; Elias Symeonakis; Jason M. Dortch; Kathleen Nesbitt (Natural Hazards, 2018)

Ecology can inform genetics: Disassortative mating contributes to MHC polymorphism in Leach’s storm‐petrels ( Oceanodroma leucorhoa ) - Brian Hoover; Miguel Alcaide; Sarah Jennings; Simon Yung Wa Sin; Scott V. Edwards; Gabrielle A. Nevitt (Molecular Ecology, 2018)
Studies of MHC‐based mate choice in wild populations often test hypotheses on species exhibiting female choice and male–male competition, which reflects the general prevalence of females as the choosy sex in natural systems. Here, we examined mutual mate‐choice patterns in a small burrow‐nesting seabird, the Leach’s storm‐petrel ( Oceanodroma leucorhoa ), using the major histocompatibility complex (MHC). The life history and ecology of this species are extreme: both partners work together to fledge a single chick during the breeding season, a task that requires regularly travelling hundreds of kilometres to and from foraging grounds over a 6‐ to 8‐week provisioning period. Using a 5‐year data set unprecedented for this species ( n = 1078 adults and 925 chicks), we found a positive relationship between variation in the likelihood of female reproductive success and heterozygosity at Ocle‐ DAB 2, a MHC class IIB locus. Contrary to previous reports rejecting disassortative mating as a mechanism for maintaining genetic polymorphism in this species, here we show that males make significant disassortative mate‐choice decisions. Variability in female reproductive success suggests that the most common homozygous females (Ocle‐ DAB 2*01/Ocle‐ DAB 2*01) may be physiologically disadvantaged and, therefore, less preferred as lifelong partners for choosy males. The results from this study support the role of mate choice in maintaining high levels of MHC variability in a wild seabird species and highlight the need to incorporate a broader ecological framework and sufficient sample sizes into studies of MHC ‐based mating patterns in wild populations in general.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

HT-2 and T-2 toxins in Norwegian oat grains related to weather conditions at different growth stages - Anne-Grete Roer Hjelkrem; Heidi Udnes Aamot; Guro Brodal; Einar C. Strand; Torfinn Torp; Simon G. Edwards; Ruth Dill-Macky; Ingerd Skow Hofgaard (European Journal of Plant Pathology, 2018)

Variation in perception of environmental change in nine Solomon Islands communities: implications for securing fairness in community-based adaptation - Jonathan Edward Ensor; Kirsten Elizabeth Abernethy; Eric Timothy Hoddy; Shankar Aswani; Simon Albert; Ismael Vaccaro; Jason Jon Benedict; Douglas James Beare (Regional Environmental Change, 2018)

Selectivity underlies the dissociation between seasonal prey availability and prey consumption in a generalist predator - Thomas D. Whitney; Michael I. Sitvarin; Edward A. Roualdes; Simon J. Bonner; James D. Harwood (Molecular Ecology, 2018)
Generalist predators are capable of selective foraging, but are predicted to feed in close proportion to prey availability to maximize energetic intake especially when overall prey availability is low. By extension, they are also expected to feed in a more frequency‐dependent manner during winter compared to the more favourable foraging conditions during spring, summer and fall seasons. For 18 months, we observed the foraging patterns of forest‐dwelling wolf spiders from the genus Schizocosa (Araneae: Lycosidae) using PCR ‐based gut‐content analysis and simultaneously monitored the activity densities of two common prey: springtails (Collembola) and flies (Diptera). Rates of prey detection within spider guts relative to rates of prey collected in traps were estimated using Roualdes’ c st model and compared using various linear contrasts to make inferences pertaining to seasonal prey selectivity. Results indicated spiders foraged selectively over the course of the study, contrary to predictions derived from optimal foraging theory. Even during winter, with overall low prey densities, the relative rates of predation compared to available prey differed significantly over time and by prey group. Moreover, these spiders appeared to diversify their diets; the least abundant prey group was consistently overrepresented in the diet within a given season. We suggest that foraging in generalist predators is not necessarily restricted to frequency dependency during winter. In fact, foraging motives other than energy maximization, such as a more nutrient‐focused strategy, may also be optimal for generalist predators during prey‐scarce winters.

Prospects for seasonal forecasting of iceberg distributions in the North Atlantic - Robert Marsh; Grant Bigg; Yifan Zhao; Matthew J. Martin; Jeffrey R. Blundell; Simon A. Josey; Edward Hanna; Vladimir Ivchenko (Natural Hazards, 2018)

Impact of agronomic and climatic factors on the mycotoxin content of harvested oats in the United Kingdom - Simon G. Edwards (Food Additives & Contaminants: Part A, 2017)

Impact of the National Cervical Screening Programme in New Zealand by age: analysis of cervical cancer trends 1985–2013 in all women and in Māori women - Megan A. Smith; Simon Edwards; Karen Canfell (Cancer Causes & Control, 2017)

DON content in oat grains in Norway related to weather conditions at different growth stages - Anne-Grete Roer Hjelkrem; Torfinn Torp; Guro Brodal; Heidi Udnes Aamot; Einar Strand; Berit Nordskog; Ruth Dill-Macky; Simon G. Edwards; Ingerd Skow Hofgaard (European Journal of Plant Pathology, 2017)

Initial biochar effects on plant productivity derive from N fertilization - Simon Jeffery; Ilse Memelink; Edward Hodgson; Sian Jones; Tess F. J. van de Voorde; T. Martijn Bezemer; Liesje Mommer; Jan Willem van Groenigen (Plant and Soil, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

The city as a refuge for insect pollinators - Damon M. Hall; Gerardo R. Camilo; Rebecca K. Tonietto; Jeff Ollerton; Karin Ahrné; Mike Arduser; John S. Ascher; Katherine C. R. Baldock; Robert Fowler; Gordon Frankie; Dave Goulson; Bengt Gunnarsson; et al. (Conservation Biology, 2017)
Research on urban insect pollinators is changing views on the biological value and ecological importance of cities. The abundance and diversity of native bee species in urban landscapes that are absent in nearby rural lands evidence the biological value and ecological importance of cities and have implications for biodiversity conservation. Lagging behind this revised image of the city are urban conservation programs that historically have invested in education and outreach rather than programs designed to achieve high‐priority species conservation results. We synthesized research on urban bee species diversity and abundance to determine how urban conservation could be repositioned to better align with new views on the ecological importance of urban landscapes. Due to insect pollinators’ relatively small functional requirements—habitat range, life cycle, and nesting behavior—relative to larger mammals, we argue that pollinators put high‐priority and high‐impact urban conservation within reach. In a rapidly urbanizing world, transforming how environmental managers view the city can improve citizen engagement and contribute to the development of more sustainable urbanization.

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Formal modelling of predator preferences using molecular gut-content analysis - Edward A. Roualdes; Simon J. Bonner; Thomas D. Whitney; James D. Harwood (Environmental and Ecological Statistics, 2016)

An integrated pan‐tropical biomass map using multiple reference datasets - Valerio Avitabile; Martin Herold; Gerard B. M. Heuvelink; Simon L. Lewis; Oliver L. Phillips; Gregory P. Asner; John Armston; Peter S. Ashton; Lindsay Banin; Nicolas Bayol; Nicholas J. Berry; Pascal Boeckx; et al. (Global Change Biology, 2016)
We combined two existing datasets of vegetation aboveground biomass ( AGB ) ( Proceedings of the National Academy of Sciences of the United States of America , 108 , 2011, 9899; Nature Climate Change , 2 , 2012, 182) into a pan‐tropical AGB map at 1‐km resolution using an independent reference dataset of field observations and locally calibrated high‐resolution biomass maps, harmonized and upscaled to 14 477 1‐km AGB estimates. Our data fusion approach uses bias removal and weighted linear averaging that incorporates and spatializes the biomass patterns indicated by the reference data. The method was applied independently in areas (strata) with homogeneous error patterns of the input (Saatchi and Baccini) maps, which were estimated from the reference data and additional covariates. Based on the fused map, we estimated AGB stock for the tropics (23.4 N–23.4 S) of 375 Pg dry mass, 9–18% lower than the Saatchi and Baccini estimates. The fused map also showed differing spatial patterns of AGB over large areas, with higher AGB density in the dense forest areas in the Congo basin, Eastern Amazon and South‐East Asia, and lower values in Central America and in most dry vegetation areas of Africa than either of the input maps. The validation exercise, based on 2118 estimates from the reference dataset not used in the fusion process, showed that the fused map had a RMSE 15–21% lower than that of the input maps and, most importantly, nearly unbiased estimates (mean bias 5 Mg dry mass ha −1 vs. 21 and 28 Mg ha −1 for the input maps). The fusion method can be applied at any scale including the policy‐relevant national level, where it can provide improved biomass estimates by integrating existing regional biomass maps as input maps and additional, country‐specific reference datasets.

Impact of post-anthesis rainfall, fungicide and harvesting time on the concentration of deoxynivalenol and zearalenone in wheat - Lalit L. Kharbikar; Edward T. Dickin; Simon G. Edwards (Food Additives & Contaminants: Part A, 2015)

Evaluation of microbial transport during aerobic bioaugmentation of an RDX-contaminated aquifer - Fiona H. Crocker; Karl J. Indest; Carina M. Jung; Dawn E. Hancock; Mark E. Fuller; Paul B. Hatzinger; Simon Vainberg; Jonathan D. Istok; Edward Wilson; Mandy M. Michalsen (Biodegradation, 2015)

Evidence‐based conservation: reply to Tepedino et al. - Gretchen Lebuhn; Sam Droege; Edward F. Connor; Barbara Gemmill‐Herren; Simon G. Potts; Robert L. Minckley; Robert P. Jean; Emanuel Kula; David W. Roubik; Karen W. Wright; Gordon Frankie; Frank Parker (Conservation Biology, 2015)

Fire in Australian savannas: from leaf to landscape - Jason Beringer; Lindsay B. Hutley; David Abramson; Stefan K. Arndt; Peter Briggs; Mila Bristow; Josep G. Canadell; Lucas A. Cernusak; Derek Eamus; Andrew C. Edwards; Bradley J. Evans; Benedikt Fest; et al. (Global Change Biology, 2015)
Savanna ecosystems comprise 22% of the global terrestrial surface and 25% of Australia (almost 1.9 million km 2 ) and provide significant ecosystem services through carbon and water cycles and the maintenance of biodiversity. The current structure, composition and distribution of Australian savannas have coevolved with fire, yet remain driven by the dynamic constraints of their bioclimatic niche. Fire in Australian savannas influences both the biophysical and biogeochemical processes at multiple scales from leaf to landscape. Here, we present the latest emission estimates from Australian savanna biomass burning and their contribution to global greenhouse gas budgets. We then review our understanding of the impacts of fire on ecosystem function and local surface water and heat balances, which in turn influence regional climate. We show how savanna fires are coupled to the global climate through the carbon cycle and fire regimes. We present new research that climate change is likely to alter the structure and function of savannas through shifts in moisture availability and increases in atmospheric carbon dioxide, in turn altering fire regimes with further feedbacks to climate. We explore opportunities to reduce net greenhouse gas emissions from savanna ecosystems through changes in savanna fire management.

Erosion rates as a potential bottom‐up control of forest structural characteristics in the Sierra Nevada Mountains - David T. Milodowski; Simon M. Mudd; Edward T. A. Mitchard (Ecology, 2015)
The physical characteristics of landscapes place fundamental constraints on vegetation growth and ecosystem function. In actively eroding landscapes, many of these characteristics are controlled by long‐term erosion rates: increased erosion rates generate steeper topography and reduce the depth and extent of weathering, limiting moisture storage capacity and impacting nutrient availability. Despite the potentially important bottom‐up control that erosion rates place on substrate characteristics, the relationship between the two is largely unexplored. We investigate spatial variations in aboveground biomass (AGB) across a structurally diverse mixed coniferous/deciduous forest with an order of magnitude erosion‐rate gradient in the Northern Californian Sierra Nevada, USA, using high resolution LiDAR data and field plots. Mean basin slope, a proxy for erosion rate, accounts for 32% of variance in AGB within our field area ( P

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Natural antisense transcripts of UL123 packaged in human cytomegalovirus virions - Cui-Qing Yang; Ling-Feng Miao; Xing Pan; Cong-Cong Wu; Simon Rayner; Edward S. Mocarski; Han-Qing Ye; Min-Hua Luo (Archives of Virology, 2014)

Land‐sharing versus land‐sparing logging: reconciling timber extraction with biodiversity conservation - David P. Edwards; James J. Gilroy; Paul Woodcock; Felicity A. Edwards; Trond H. Larsen; David J. R. Andrews; Mia A. Derhé; Teegan D. S. Docherty; Wayne W. Hsu; Simon L. Mitchell; Takahiro Ota; Leah J. Williams; et al. (Global Change Biology, 2014)
Selective logging is a major driver of rainforest degradation across the tropics. Two competing logging strategies are proposed to meet timber demands with the least impact on biodiversity: land sharing, which combines timber extraction with biodiversity protection across the concession; and land sparing, in which higher intensity logging is combined with the protection of intact primary forest reserves. We evaluate these strategies by comparing the abundances and species richness of birds, dung beetles and ants in Borneo, using a protocol that allows us to control for both timber yield and net profit across strategies. Within each taxonomic group, more species had higher abundances with land‐sparing than land‐sharing logging, and this translated into significantly higher species richness within land‐sparing concessions. Our results are similar when focusing only on species found in primary forest and restricted in range to Sundaland, and they are independent of the scale of sampling. For each taxonomic group, land‐sparing logging was the most promising strategy for maximizing the biological value of logging operations.

Developing logistic models to relate the accumulation of DON associated with Fusarium head blight to climatic conditions in Europe - Xiangming Xu; Laurence V. Madden; Simon G. Edwards; Fiona M. Doohan; Antonio Moretti; L. Hornok; P. Nicholson; A. Ritieni (European Journal of Plant Pathology, 2013)

Erratum to: The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; H. John B. Birks; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; et al. (Vegetation History and Archaeobotany, 2013)

The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; Barbara A. Brayshay; et al. (Vegetation History and Archaeobotany, 2013)

Trophic Flexibility and the Persistence of Understory Birds in Intensively Logged Rainforest - DAVID P. EDWARDS; PAUL WOODCOCK; ROB J. NEWTON; FELICITY A. EDWARDS; DAVID J. R. ANDREWS; TEEGAN D. S. DOCHERTY; SIMON L. MITCHELL; TAKAHIRO OTA; SUZAN BENEDICK; SIMON H. BOTTRELL; KEITH C. HAMER (Conservation Biology, 2013)
Effects of logging on species composition in tropical rainforests are well known but may fail to reveal key changes in species interactions. We used nitrogen stable‐isotope analysis of 73 species of understory birds to quantify trophic responses to repeated intensive logging of rainforest in northern Borneo and to test 4 hypotheses: logging has significant effects on trophic positions and trophic‐niche widths of species, and the persistence of species in degraded forest is related to their trophic positions and trophic‐niche widths in primary forest. Species fed from higher up the food chain and had narrower trophic‐niche widths in degraded forest. Species with narrow trophic‐niche widths in primary forest were less likely to persist after logging, a result that indicates a higher vulnerability of dietary specialists to local extinction following habitat disturbance. Persistence of species in degraded forest was not related to a species’ trophic position. These results indicate changes in trophic organization that were not apparent from changes in species composition and highlight the importance of focusing on trophic flexibility over the prevailing emphasis on membership of static feeding guilds. Our results thus support the notion that alterations to trophic organization and interactions within tropical forests may be a pervasive and functionally important hidden effect of forest degradation. Flexibilidad Trófica y la Persistencia de Aves de Sotobosque en un Bosque Lluvioso Talado Intensivamente

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Neuron-Specific Expression of Tomosyn1 in the Mouse Hippocampal Dentate Gyrus Impairs Spatial Learning and Memory - Boaz Barak; Eitan Okun; Yoav Ben-Simon; Ayal Lavi; Ronit Shapira; Ravit Madar; Yue Wang; Eric Norman; Anton Sheinin; Mario A. Pita; Ofer Yizhar; Mohamed R. Mughal; et al. (NeuroMolecular Medicine, 2013)

Genetic characterization and mapping of the Rht-1 homoeologs and flanking sequences in wheat - Edward P. Wilhelm; Rhian M. Howells; Nadia Al-Kaff; Jizeng Jia; Catherine Baker; Michelle A. Leverington-Waite; Simon Griffiths; Andy J. Greenland; Margaret I. Boulton; Wayne Powell (Theoretical and Applied Genetics, 2013)

Cigarette smoking and risk of ovarian cancer: a pooled analysis of 21 case–control studies - Mette T. Faber; Susanne K. Kjær; Christian Dehlendorff; Jenny Chang-Claude; Klaus K. Andersen; Estrid Høgdall; Penelope M. Webb; Susan J. Jordan; Mary Anne Rossing; Jennifer A. Doherty; Galina Lurie; Pamela J. Thompson; et al. (Cancer Causes & Control, 2013)

Crops that feed the world 9. Oats- a cereal crop for human and livestock feed with industrial applications - Athole Marshall; Sandy Cowan; Simon Edwards; Irene Griffiths; Catherine Howarth; Tim Langdon; Ethel White (Food Security, 2013)

Detecting Insect Pollinator Declines on Regional and Global Scales - Gretchen Lebuhn; Sam Droege; Edward F. Connor; Barbara Gemmill‐Herren; Simon G. Potts; Robert L. Minckley; Terry Griswold; Robert Jean; Emanuel Kula; David W. Roubik; Jim Cane; Karen W. Wright; et al. (Conservation Biology, 2013)
Recently there has been considerable concern about declines in bee communities in agricultural and natural habitats. The value of pollination to agriculture, provided primarily by bees, is >$200 billion/year worldwide, and in natural ecosystems it is thought to be even greater. However, no monitoring program exists to accurately detect declines in abundance of insect pollinators; thus, it is difficult to quantify the status of bee communities or estimate the extent of declines. We used data from 11 multiyear studies of bee communities to devise a program to monitor pollinators at regional, national, or international scales. In these studies, 7 different methods for sampling bees were used and bees were sampled on 3 different continents. We estimated that a monitoring program with 200–250 sampling locations each sampled twice over 5 years would provide sufficient power to detect small (2–5%) annual declines in the number of species and in total abundance and would cost U.S.$2,000,000. To detect declines as small as 1% annually over the same period would require >300 sampling locations. Given the role of pollinators in food security and ecosystem function, we recommend establishment of integrated regional and international monitoring programs to detect changes in pollinator communities. Detección de Declinaciones de Insectos Polinizadores a Escalas Regional y Global

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Diabetes and risk of pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium - Joanne W. Elena; Emily Steplowski; Kai Yu; Patricia Hartge; Geoffrey S. Tobias; Michelle J. Brotzman; Stephen J. Chanock; Rachael Z. Stolzenberg-Solomon; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Kathy Helzlsouer; Eric J. Jacobs; et al. (Cancer Causes & Control, 2013)

Trait-dependent declines of species following conversion of rain forest to oil palm plantations - Michael J. M. Senior; Keith C. Hamer; Simon Bottrell; David P. Edwards; Tom M. Fayle; Jennifer M. Lucey; Peter J. Mayhew; Robert Newton; Kelvin S.-H. Peh; Frederick H. Sheldon; Christopher Stewart; Alison R. Styring; et al. (Biodiversity and Conservation, 2013)

Rapid magmatic processes accompany arc–continent collision: the Western Bismarck arc, Papua New Guinea - Heather Cunningham; Jim Gill; Simon Turner; John Caulfield; Louise Edwards; Simon Day (Contributions to Mineralogy and Petrology, 2012)

Quantification of the relationship between the environment and Fusarium head blight, Fusarium pathogen density, and mycotoxins in winter wheat in Europe - Alissa B. Kriss; Pierce A. Paul; Xiangming Xu; Paul Nicholson; Fiona M. Doohan; Laszlo Hornok; Alberto Rietini; Simon G. Edwards; Laurence V. Madden (European Journal of Plant Pathology, 2012)

Assessing trophic position from nitrogen isotope ratios: effective calibration against spatially varying baselines - Paul Woodcock; David P. Edwards; Rob J. Newton; Felicity A. Edwards; Chey Vun Khen; Simon H. Bottrell; Keith C. Hamer (The Science of Nature, 2012)

Influence of insects and fungal pathogens on individual and population parameters of Cirsium arvense in its native and introduced ranges - Michael G. Cripps; Graeme W. Bourdôt; David J. Saville; Hariet L. Hinz; Simon V. Fowler; Grant R. Edwards (Biological Invasions, 2011)

The geochemistry of primary and weathered oil shale and coquina across the Julia Creek vanadium deposit (Queensland, Australia) - Stephen Edward Lewis; Robert A. Henderson; Gerald R. Dickens; Graham A. Shields; Simon Coxhell (Mineralium Deposita, 2010)

Enemy release does not increase performance of Cirsium arvense in New Zealand - Michael G. Cripps; Grant R. Edwards; Graeme W. Bourdôt; David J. Saville; Hariet L. Hinz; Simon V. Fowler (Plant Ecology, 2010)

The high value of logged tropical forests: lessons from northern Borneo - Nicholas J. Berry; Oliver L. Phillips; Simon L. Lewis; Jane K. Hill; David P. Edwards; Noel B. Tawatao; Norhayati Ahmad; David Magintan; Chey V. Khen; M. Maryati; Robert C. Ong; Keith C. Hamer (Biodiversity and Conservation, 2010)

Evaluation of pathogenicity and aggressiveness of F. langsethiae on oat and wheat seedlings relative to known seedling blight pathogens - Samuel M. Imathiu; Martin C. Hare; Rumiana V. Ray; Matthew Back; Simon G. Edwards (European Journal of Plant Pathology, 2010)

Hierarchical Annealing for Synthesis of Binary Images - Simon K. Alexander; Paul Fieguth; Marios A. Ioannidis; Edward R. Vrscay (Mathematical Geosciences, 2009)

Fusarium langsethiae pathogenicity and aggressiveness towards oats and wheat in wounded and unwounded in vitro detached leaf assays - Samuel M. Imathiu; Rumiana V. Ray; Matthew Back; Martin C. Hare; Simon G. Edwards (European Journal of Plant Pathology, 2009)

Extreme changes to gene expression associated with homoploid hybrid speciation - MATTHEW J. HEGARTY; GARY L. BARKER; ADRIAN C. BRENNAN; KEITH J. EDWARDS; RICHARD J. ABBOTT; SIMON J. HISCOCK (Molecular Ecology, 2009)
Hybridization is an important cause of abrupt speciation. Hybrid speciation without a change in ploidy (homoploid hybrid speciation) is well‐established in plants but has also been reported in animals and fungi. A notable example of recent homoploid hybrid speciation is Senecio squalidus (Oxford ragwort), which originated in the UK in the 18th Century following introduction of hybrid material from a hybrid zone between S. chrysanthemifolius and S. aethnensis on Mount Etna, Sicily. To investigate genetic divergence between these taxa, we used complementary DNA microarrays to compare patterns of floral gene expression. These analyses revealed major differences in gene expression between the parent species and wild and resynthesized S. squalidus . Comparisons of gene expression between S. aethnensis , S. chrysanthemifolius and natural S. squalidus identified genes potentially involved in local environmental adaptation. The analysis also revealed non‐additive patterns of gene expression in the hybrid relative to its progenitors. These expression changes were more dramatic and widespread in resynthesized hybrids than in natural S. squalidus , suggesting that a unique expression pattern may have been fixed during the allopatric divergence of British S. squalidus . We speculate that hybridization‐induced gene‐expression change may provide an immediate source of novel phenotypic variation upon which selection can act to facilitate homoploid hybrid speciation in plants.

Polymorphic Variants of Extracellular Superoxide Dismutase Gene in a Romanian Population with Atheroma - Olguta C. Samoila; Angela M. Carter; Simon T. Futers; Gabriela Otiman; Andrei Anghel; Liviu Tamas; Edward Seclaman (Biochemical Genetics, 2008)

Diagnosis and management of small‐scale fisheries in developing countries - Neil L Andrew; Christophe Béné; Stephen J Hall; Edward H Allison; Simon Heck; Blake D Ratner (Fish and Fisheries, 2007)
Small‐scale fisheries (SSF) make important but undervalued contributions to the economies of some of the world’s poorest countries. They also provide much of the animal protein needed by societies in which food security remains a pressing issue. Assessment and management of these fisheries is usually inadequate or absent and they continue to fall short of their potential as engines for development and social change. In this study, we bring together existing theory and methods to suggest a general scheme for diagnosing and managing SSF. This approach can be adapted to accommodate the diversity of these fisheries in the developing world. Many threats and solutions to the problems that beset SSF come from outside the domain of the fishery. Significant improvements in prospects for fisheries will require major changes in societal priorities and values, with consequent improvements in policy and governance. Changes in development policy and science reflect these imperatives but there remains a need for intra‐sectoral management that builds resilience and reduces vulnerability to those forces beyond the influence of small‐scale fishers.

Comparative genomics reveals functional transcriptional control sequences in the Prop1 gene - Robert D. Ward; Shannon W. Davis; MinChul Cho; Constance Esposito; Robert H. Lyons; Jan-Fang Cheng; Edward M. Rubin; Simon J. Rhodes; Lori T. Raetzman; Timothy P. L. Smith; Sally A. Camper (Mammalian Genome, 2007)

Impairment of specific episodic memory processes by sub-psychotic doses of ketamine: the effects of levels of processing at encoding and of the subsequent retrieval task - Garry D. Honey; Rebekah A. E. Honey; Sam R. Sharar; Danielle C. Turner; Edith Pomarol-Clotet; Dharshan Kumaran; Jon S. Simons; Xiangen Hu; Michael D. Rugg; Edward T. Bullmore; Paul C. Fletcher (Psychopharmacology, 2005)

Book Review: An overview on toxigenic fungi and mycotoxins in Europe. Antonio Logrieco and Angelo Visconti. 252 pp. Kluwer Academic Publishers, Dordrecht, The Netherlands. ISBN 1-4020-2645-5. €95.00; US$119.00; £66.00. - Simon Edwards (European Journal of Plant Pathology, 2005)

Development of anonymous cDNA microarrays to study changes to the Senecio floral transcriptome during hybrid speciation - MATTHEW J. HEGARTY; JOANNA M. JONES; IAN D. WILSON; GARY L. BARKER; JANE A. COGHILL; PATRICIA SANCHEZ‐BARACALDO; GUOQING LIU; RICHARD J. A. BUGGS; RICHARD J. ABBOTT; KEITH J. EDWARDS; SIMON J. HISCOCK (Molecular Ecology, 2005)
Interspecific hybridization is an important process through which abrupt speciation can occur. In recent years, genetic changes associated with hybrid speciation have been identified through a variety of techniques, including AFLP/SSR mapping, GISH/FISH and cDNA‐AFLP differential display. However, progress in using microarray technology to analyse whole genome/transcriptome changes associated with hybrid speciation has been limited due to the lack of extensive sequence data for many hybrid species and the difficulties in extrapolating results from commercially available microarrays for model species onto nonmodel hybrid taxa. Increasingly therefore researchers studying nonmodel systems are turning to the development of ‘anonymous’ cDNA microarrays, where the time and cost of producing microarrays is reduced by printing unsequenced cDNA clones, and sequencing only those clones that display interesting expression patterns. Here we describe the creation, testing and preliminary use of anonymous cDNA microarrays to study changes in floral transcriptome associated with allopolyploid speciation in the genus Senecio. We report a comparison of gene expression between the allohexaploid hybrid, Senecio cambrensis , its parental taxa Senecio squalidus (diploid) and Senecio vulgaris (tetraploid), and the intermediate triploid (sterile) hybrid Senecio × baxteri . Anonymous microarray analysis revealed dramatic differences in floral gene expression between these four taxa and demonstrates the power of this technique for studies of the genetic impact of hybridization in nonmodel flowering plants.

Climate variability and campylobacter infection: an international study - R. Sari Kovats; Sally J. Edwards; Dominique Charron; John Cowden; Rennie M. D’Souza; Kristie L. Ebi; Charmaine Gauci; Peter Gerner-Smidt; Shakoor Hajat; Simon Hales; Gloria Hernández Pezzi; Bohumir Kriz; et al. (International Journal of Biometeorology, 2005)

The gene encoding the ribulose monophosphate pathway enzyme, 3-hexulose-6-phosphate synthase, from Aminomonas aminovorus C2A1 is adjacent to coding sequences that exhibit similarity to histidine biosynthesis enzymes. - Edward J. Taylor; Nicola L. Smith; John Colby; Simon J. Charnock; Gary W. Black (Antonie van Leeuwenhoek, 2004)

Strategies for the Control of Fusarium Head Blight in Cereals - Stoyan R. Pirgozliev; Simon G. Edwards; Martin C. Hare; Peter Jenkinson (European Journal of Plant Pathology, 2003)

CD2F-10: a new member of the CD2 subset of the immunoglobulin superfamily - Janet A. Fennelly; Bela Tiwari; Simon J. Davis; Edward J. Evans (Immunogenetics, 2001)

The effect of motor learning in facioscapulohumeral muscular dystrophy patients - Amir H. Bakhtiary; Joanne Phoenix; Richard H. T. Edwards; Simon P. Frostick (European Journal of Applied Physiology, 2000)

The effect of lethal copper solutions on the behavior of rainbow trout,Salmo gairdneri - Simon C. J. Pedder; Edward J. Maly (Archives of Environmental Contamination and Toxicology, 1985)